The Photocatalytic Application of Semiconductor Stibnite Nanostructure Synthesized via a Simple Microwave-Assisted Approach in Propylene Glycol for Degradation of Dye Pollutants and its Optical Property - Eksuree Saksornchai (2018)
© 2017, The Author(s). Stibnite (Sb2S3) semiconducting material was successfully synthesized by a rapid and facile microwave route using antimony chloride (SbCl3) and sodiumthiosulfate (Na2S2O3) dissolved in propylene glycol (PG) containing different hydroxyethyl cellulose (HEC) masses. The phase identification, morphology, and elemental composition of products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), field- emission scanning electron microscopy (FE-SEM), energy dispersive X-ray (EDX) spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The results revealed the orthorhombic phase of Sb2S3single crystal-forming sheaf-like nanostructure, and a possible formation mechanism was proposed and discussed. Its direct band gap calculated from UV-visible absorption is 1.60 eV. In this research, the photocatalytic activities of Sb2S3nanostructure were investigated through the degradation of methyl orange (MO) and methylene blue (MB) under visible light irradiation. The as-obtained 0.30 g HEC-added solution (0.3 HEC-Sb2S3) photocatalyst exhibited better photocatalytic activity than the other products, which degraded 91% of MO within 300 min and 90% of MB within 240 min under the Xe-lamp irradiation. The first-order plot was fitted with this experiment which the rate constant (k) of 0.3 HEC-Sb2S3for MO and MB degradation are 0.0085 and 0.0098 min−1, respectively. Therefore, the new experience with a novel and simple synthetic procedure of Sb2S3photocatalyst that exhibits the characteristics of a highly effective photocatalyst under visible light irradiation was discovered.